2022
DOI: 10.3389/fcell.2022.804419
|View full text |Cite
|
Sign up to set email alerts
|

STIL Acts as an Oncogenetic Driver in a Primary Cilia-Dependent Manner in Human Cancer

Abstract: SCL/TAL1 Interrupting locus (STIL) is a ciliary-related gene involved in regulating the cell cycle and duplication of centrioles in dividing cells. STIL has been found disordered in multiple cancers and driven carcinogenesis. However, the molecular mechanisms and biological functions of STIL in cancers remain ambiguous. Here, we systematically analyzed the genetic alterations, molecular mechanisms, and clinical relevance of STIL across >10,000 samples representing 33 cancer types in The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…S2A–D). A previous study has shown that PC is closely related to the cell cycle [ 16 , 21 ]. IFT88 also has been demonstrated to play a crucial role in regulating the cell cycle [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S2A–D). A previous study has shown that PC is closely related to the cell cycle [ 16 , 21 ]. IFT88 also has been demonstrated to play a crucial role in regulating the cell cycle [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 F), we called them prognosis-related PC genes (PRPGs). We first focus on STIL, which has been found to influence cell cycle progression by regulating the PC in kidney and prostate cancer in our previous study [ 16 ]. In the TCGA-BLCA dataset, STIL mRNA expression was up-regulated in tumour tissue, and the patients with high STIL expression showed a worse prognosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In liver cancer, low expression of KIF20A inhibits cell proliferation, promotes chemosensitivity, and is associated with a better prognosis ( 53 ). STIL acts as an oncogene driver in a primary cilia-dependent manner in human cancer ( 54 ). STIL is integral in regulating cancer cell motility through plate oval accumulation of the ARHGEF7-PAK1 complex ( 55 ).…”
Section: Discussionmentioning
confidence: 99%